SALMONELLA IN POULTRY FEEDS IN BRAZIL - Berchieri, A.; Fernandes, S. A.; Irino, K.; Quintana, J. L.; Santos, A. J. (Soc Brasileira Microbiologia, 1993)
This experiment was undertaken to determine the possible presence of Salmonella in poultry diets. A total of two hundred samples of ration from 4 commercial poultry feed industries were examined. The results revealed the presence of salmonellae in 10% of the samples studied and 14 serotypes were identified. The procedure for Salmonella isolation included the pre-enrichment step and the strains were submitted to antimicrobial tests. The 29 strains were resistant to the followings antimicrobial agents (% of resistance in parenthesis): Erythromycin (100%), sulphonamides (100%), colistin (100%), streptomycin (100%), bacitracin (100%), penicillin (100%), tetracycline (92,9%), cephalothin (75%), carbenicillin (62,5%), ampicillin (46,5%), kanamycin (46,5%), nitrofurantoin (39,3%), neomycin (25%), amikacin (21,4%), sulphazotrin (21,4%), nalidix acid (18,8%), chloramphenycol (17,9%), linco-spectin (17,9%), gentamicin (17,9%), and cefoxitin (6,3%).
Keywords: SALMONELLA; ISOLATION; POULTRY FEEDS; ANTIMICROBIALS